Chemical Composition and Quality Parameters of Citronella (Cymbopogon nardus) Essential Oil Based on GC–MS and Physicochemical Analysis - Ramadhan, Dwi Sapri; Warsito; Silvianti, Risna; Cahayo, Maf'ud; Azzahra, Vina Octavia (Universitas Negeri Medan, 2026)
Citronella (Cymbopogon nardus (L.) Rendle) essential oil is widely utilized in the perfume, cosmetic, and pharmaceutical industries, primarily due to its high content of citronellal, geraniol, and citronellol. This study aimed to evaluate the chemical composition and quality parameters of citronella essential oil using gas chromatography–mass spectrometry (GC–MS) and physicochemical analysis. The oil sample was obtained by steam distillation of fresh leaves and subsequently characterized in terms of specific gravity, refractive index, optical rotation, and flash point, while the chemical composition was determined based on GC–MS chromatogram peak areas. The physicochemical analysis showed a specific gravity of 0.894, refractive index of 1.477, optical rotation of −6.59°, and a flash point above 80 °C, indicating compliance with quality standards for citronella essential oil. GC–MS analysis identified 21 compounds, with trans-geraniol (70.65%), geranyl acetate (7.70%), β-citronellol (3.17%), and citronellal (1.78%) as the major constituents. These findings confirm that steam-distilled citronella essential oil exhibits good quality and a chemical profile that supports its potential for essential oil-based industrial applications.